Geothermal power plants of the Soviet Union. A technical survey of existing and planned installations - DiPippo, R. (Southeastern Massachusetts Univ., North Dartmouth (USA), 1979)
Some of the geothermal areas in the Soviet Union which may support electric generating stations are described. The plants at Pauzhetka (single-flash steam), at Paratunka (Freon binary), and at Bolshoye-Bannoye (multi-flash steam) are described in technical detail. The reference list contains some of the most recent sources of information on geothermal power plant developments in the Soviet Union.